Survival benefits of primary tumor resection in metastatic differentiated thyroid cancer: an analysis of SEER data - Jiaqiang Dan; Jingya Tan; Yao Guo; Xin Lu; Ying Leng; Renxi Tang; Junyan Li; Junhua Huang (Scientific Reports)
Abstract Metastatic differentiated thyroid cancer (mDTC) can exhibit aggressive growth and disseminate to distant organs, thereby reducing survival rates. The benefits of primary tumor resection (PTR) for patients with mDTC are still debated. In this study, we utilized the Surveillance, Epidemiology, and End Results (SEER) database to evaluate mDTC patients, focusing on the impact of organ-specific metastases and the number of metastatic sites on prognosis, as well as the potential efficacy of PTR as a therapeutic intervention. 904 patients with mDTC at initial diagnosis from 2010 to 2015 were studied. Lung and bone were the most common sites of metastasis. Patients with brain, lung and liver metastasis had significantly worse overall survival (OS) (all p < 0.05) and cancer-specific survival (CSS) (all p < 0.05). Among all the patients, 550 (60.84%) underwent PTR, which was associated with reduced risk of overall mortality (OM) and cancer-specific mortality (CSM) (all p < 0.05). When analyzing different metastatic patterns, PTR significantly lowered the risk of OM and CSM for patients with bone, brain, lung, liver, or distant lymph node (DLN) involvement (all p < 0.05). Surgical resection also improved OS and CSS (both p < 0.05) in patients with multiple organ involvement or one/two metastases. Our findings suggest that PTR may confer benefits to select individuals with metastatic DTC. To validate these results and facilitate their integration into clinical practice, multicenter prospective studies are warranted.